2005
DOI: 10.1176/appi.ps.56.6.678
|View full text |Cite
|
Sign up to set email alerts
|

High Utilizers of Psychiatric Emergency Services

Abstract: High utilizers make up a small percentage of individuals who seek care in psychiatric emergency services and disproportionately use resources. It may be helpful to use two definitions of high utilizer to identify patients at different phases of their illness and to guide clinical interventions and mental health policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
135
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(158 citation statements)
references
References 14 publications
13
135
2
8
Order By: Relevance
“…However, these frequent attenders accounted for a substantial proportion of such attendances. These findings are similar to those of Pasic et al 5 We also found that frequent attenders had longer psychiatric histories, higher rates of schizophrenia, and were more likely to be prescribed antipsychotics, but had equal gender distribution as compared with single attenders. Chaput & Lebel 6 reported similar findings in their study of similar patient population.…”
Section: Discussionsupporting
confidence: 91%
“…However, these frequent attenders accounted for a substantial proportion of such attendances. These findings are similar to those of Pasic et al 5 We also found that frequent attenders had longer psychiatric histories, higher rates of schizophrenia, and were more likely to be prescribed antipsychotics, but had equal gender distribution as compared with single attenders. Chaput & Lebel 6 reported similar findings in their study of similar patient population.…”
Section: Discussionsupporting
confidence: 91%
“…3 These people access mental health services younger and more frequently than people with psychiatric disorders but no DD 4,5 and are frequent users of EDs. 6 It has been suggested that ED visits by people with psychiatric disorders with DD occur, in part, because other resources are inadequate 7,8 and thus serve as a barometer of the adequacy of primary and specialty outpatient care. A recent study found that lack of primary care predicted ED use in a sample of adults with DD experiencing psychiatric crisis, when adjusting for age, sex, residential setting, and disability severity.…”
Section: Abbreviationsmentioning
confidence: 99%
“…49 On the other hand, PESs are the reference units where non-hospital services are insufficient or inexistent, 50 with a significant association existing between problems in the functioning of the outpatient mental health network and the increased number of hospitalizations and re-hospitalizations 51 and the number of visits to PESs. 52 Since PESs work 24 hours a day and usually offer free access, it is natural that unassisted patients and their relatives overload these facilities, which in turn have to deal with the exceeding demand of inefficient outpatient services. 53 Factors that are intrinsically related to the functioning of outpatient services, such as restricted multiprofessional assistance, 54 limited therapeutic proposals, 55 vacancy shortage, 56 medication availability issues, and overload due to demands related to the justice system 57 imply difficulties for the stabilization of patients in acute episodes.…”
Section: Psychiatric Emergency and Outpatient Servicesmentioning
confidence: 99%